Investigation of surface morphology and properties of Aluminium alloy oxide composite coating incorporated with Carbon nanotubes and Graphene nanoplatelets - Nazila, Nik Hafizuddin Effandi; Zakaria, Hasnol Hadi; Tan, Sin Tee; Mamat, Md Shuhazlly; Liza, Shahira; Sulaiman, Mohd Hafis; Chan, Kar Fei; Tanemura, Masaki; Yaakob, Yazid (Elsevier Editora Ltda, 2026)
Graphene Nanoplatelets (GNPs) and Carbon Nanotubes (CNTs) offer excellent properties but often suffer agglomeration when used individually. This work investigates hybridizing CNTs and GNPs as reinforcement strategy to improve dispersion and enhance the surface and mechanical properties of Anodic Aluminium Oxide (AAO). Composite coatings were fabricated by incorporating 5g of CNT:GNP mixtures with varying ratios under specific anodizing conditions (60 min in 20 % diluted H2SO4). XRD analysis confirmed that AAO and carbon-reinforced AAO composites exhibited orthorhombic and γ-Al2O3 phases with no detrimental phase transformations caused by carbon addition. Surface morphology characterization using a 3D Profiler showed that the hybrid 0.5CNT:0.5GNP produced surface roughness of (5.701 μm) and pore dimensions (w: 50.10 μm and d: 60.13 μm) lower than AAO and AAOCNT. SEM-EDX analysis further verified these findings, indicating that CNT-GNP incorporation effectively reduces porosity. The Vicker hardness of 0.5CNT:0.5GNP showed the highest value of 240.3 HV, outperforming AAO (133 HV), AAOCNT (186.2 HV), and AAOGNP (171 HV). The superior performance of the hybrid composite demonstrates that combining CNTs and GNPs effectively mitigates agglomeration and significantly enhances the structural integrity of AAO coatings. These findings provide new insights into carbon-reinforced AAO fabrication and highlight the potential of CNT-GNP hybrids for advanced surface engineering of aluminium alloys.